ANALISIS PENGARUH REKRUTMEN,KARAKTERISTIK INDIVIDUAL DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA KARYAWAN CV. GAGAK HITAM BONDOWOSO - ramadhan, wildan aditya (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2021)
Competition in business today requires companies to have quality employees. Employee performance at CV. Gagak Hitam Bondowoso has decreased, therefore it must be considered related to recruitment, namely individual obligations and further the organization. This study aims to analyze the effect of recruitment (X1), individual characteristics (X2) and further organizational commitment (X3) on employee performance (Y) on CV. Gagak Hitam Bondowos. The sample was obtained by purposive random sampling method, and 74 employee respondents were selected as the sample. While the data analysis used in this study includes: data quality test, classical assumption test, multiple linear regression analysis and hypothesis testing. The results of the partial significant test (t statistical test) from the analysis and discussion of the study show that: the recruitment regression coefficient value is 0.309 with a p-value of 0.01 (<0.05) so that Recruitment (X1) has a positive effect on Employee Performance (Y) . The regression coefficient value for Individual Characteristics (X2) is 0.345 with a p-value of 0.00 (<0.05) so that Individual Characteristics (X2) has a positive effect on Employee Performance (Y). The coefficient value of Organizational Commitment is 0.699 with a p-value of 0.00 (<0.05) so that Organizational Commitment (X3) has a positive effect on Employee Performance (Y). The F value is 23.699 with a p-value of 0.000 (<0.05) so that simultaneously (together) Recruitment (X1), Individual Characteristics (X2), and Organizational Commitment (X3) have a positive influence on Employee Performance (Y) CV . Gagak Hitam Bondowoso.